Analysis of Pressure Vessel Design on Radiator Cooling System Using Low Carbon Steel Material - Nana Rahdiana; Sukarman Sukarman; Murtalim Murtalim; Khoirudin Khoirudin; Dodi Mulyadi; Amir Amir; Tito Chaerul Pratama; Ahmad Hidayat (Journal of Applied Sciences and Advanced Technology, 2021)
This study discusses the analysis of a pressure vessel's design in the Radiator Cooling 1000 (RC-1000) system, which operates at a design temperature of 100oC. A pressure vessel is a container of gaseous, solid, or liquid material subjected to internal or external pressure and can withstand various other load variations. The pressure vessel on the RC-1000 system has a diameter of 85.4 mm or 3.36 inches and will experience an internal pressure of about 143.7 kPa or 20.84 psi, so it must be designed safely. This research method uses analytical and experimental methods. The analytical method is used to calculate the thickness of the pressure vessel material, the maximum allowable working pressure, and the hydrostatic test calculation. While the experimental method was carried out on the hydrostatic test process, the evaluation was based on the prevailing regulations in the Republic of Indonesia. Using the SPCC-SD material (JIS 3141), it was found that the minimum thickness of this pressure vessel is 1.15 mm or 0.0452 inches on the shell side and 1.10 mm or 0.0434 inches on the head/dome side. The thickness of the material used on the shell side and head/dome is 1.2 mm or 0.0472 inches in practice. This pressure vessel has passed the hydrostatic test at 1600 kPa or 232.1 psi. The test pressure is given around seven psi higher because it makes it easier to read the scale on the pressure gauge.